Induced Hyperlipidemia in Adult Male Rats and Treated by using Rosmarinus officinalis Aqueous Extract - Marwa Karim Taha; Mohammed Salman Dalas; Ahmed Hamad Saleh (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current work was goaled to revealed anti-hyperlipidemia activity of R. officinalis extract. This workutilized 20 male rats that divided to negative group; positive group was given drinking water containing0.5% H2O2 and (1%) cholesterol for 60 days. Third group: hyperlipidemia rats were treated with (50mg/kg/daily) extract. Fourth group: hyperlipidemia rats were treated with (100mg/kg/daily) extract. Theoutcomes revealed significant (P < 0.05) rise in cholesterol and triglyceride and reduce the HDL in positivegroup compare with negative group. Malonedialdehyied (MDA) was increased with reduce in glutathione(GSH) compare with negative group. Otherwise, diameters of aorta artery show significant (P < 0.05) risecompare with negative group. R. officinalis aqueous extract when used in treatment, the outcomes exhibitedimprovement in lipid profile, MDA, GSH and diameters of aorta artery compare with negative group. It wasconcluded that R. officinalis extract possess anti-hyperlipidemia activity.